Risk factors and peripheral biomarkers for schizophrenia spectrum disorders: an umbrella review of meta‐analyses. (30th December 2017) - Belbasis, L.; Köhler, C. A.; Stefanis, N.; Stubbs, B.; van Os, J.; Vieta, E.; Seeman, M. V.; Arango, C.; Carvalho, A. F.; Evangelou, E.
Abstract : Objective: This study aimed to systematically appraise the meta‐analyses of observational studies on risk factors and peripheral biomarkers for schizophrenia spectrum disorders. Methods: We conducted an umbrella review to capture all meta‐analyses and Mendelian randomization studies that examined associations between non‐genetic risk factors and schizophrenia spectrum disorders. For each eligible meta‐analysis, we estimated the summary effect size estimate, its 95% confidence and prediction intervals and the I 2 metric. Additionally, evidence for small‐study effects and excess significance bias was assessed. Results: Overall, we found 41 eligible papers including 98 associations. Sixty‐two associations had a nominally significant ( P ‐value <0.05) effect. Seventy‐two of the associations exhibited large or very large between‐study heterogeneity, while 13 associations had evidence for small‐study effects. Excess significance bias was found in 18 associations. Only five factors (childhood adversities, cannabis use, history of obstetric complications, stressful events during adulthood, and serum folate level) showed robust evidence. Conclusion: Despite identifying 98 associations, there is only robust evidence to suggest that cannabis use, exposure to stressful events during childhood and adulthood, history of obstetric complications, and low serum folate level confer a higher risk for developing schizophrenia spectrum disorders. The evidence on peripheral biomarkers for schizophrenia spectrum disorders remains limited.